Ethics: What is the Research Scenario in the Brazilian Symposium SBIE? - Carvalho, Luiz Paulo; Suzano, José Antônio; Oliveira, Jonice; Gasparini, Isabela; Santoro, Flavia Maria (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na Educação, 2021)
There is no doubt about the relevance of Computing in Education (CE), especially after the COVID-19 pandemic. However, the more we deal with computational artifacts in Education, the more we will have to face ethical dilemmas and concerns behind the engineering of the educational artifact and its values and qualities. In the context of the Brazilian Symposium on Computers in Education (SBIE), this paper aims to answer the question: what is the panorama of the occurrence of ethical aspects in SBIE publications between 2011-2020? To answer this question, we followed the methodology of Systematic Literature Review. We analyze topics such as Informed Consent, Ethics Committee, technological domains, ethical principles, and research contexts.